IMPLEMENTASI NILAI-NILAI KONSERVASI SOSIAL DALAM PERKULIAHAN PADA PROGRAM STUDI ILMU SEJARAH FIS UNNES - Purnomo, Arif (Forum Ilmu Sosial, 2015)
This research was aimed to discuss implementation of social conservation in history study program, especially in lesson plan and teaching leraning process. This research used qualitatif method. Focus of research are lecturer, students and lesson plan in history study program. Data anayses used qualitative interactive models Miles and Huberman.Â Based from research, can be concuded that implementation of characters social conservation in lesson plan depend on lecturer style in teaching learning process so that there is not the same models.